ANALYZING THE INFLUENCE OF AGE, GENDER AND EDUCATIONAL BACKGROUND ON EMPLOYEE PERFORMANCE: AT NORTH SULAWESI ELECTION SUPERVISORY BODY - Tatulus, Natalsya Christin; Rogi, Mirah Helen (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
This study examines the influence of age, gender, and educational background on employee performance at the Provincial Election Supervisory Board (BAWASLU) of North Sulawesi. Using a quantitative approach with a saturated sampling method involving 48 respondents, data were analyzed through multiple linear regression using SPSS. The results show that age has a significant and positive effect on employee performance, while gender and educational background have no significant effect. However, when tested simultaneously, age, gender, and educational background together have a significant impact on performance. These findings indicate that employee performance at Bawaslu is mainly influenced by age and experience, emphasizing the importance of managing workforce diversity in public institutions.   Keywords: Age, Gender, Educational Background, Employee Performance